PENGARUH LATIHAN HIGH INTENSITY INTERVAL TRAINING (HIIT) TERHADAP PENINGKATAN VO2MAX ATLET - Khapipudin, Khapipudin; Yusuf, Putra Muhammad; Susilawati, Indri (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2022)
The VO2Max level of the futsal athletes of SMAN 1 Gerung is included in the low category, this can be seen when the players during the match quickly experience fatigue. The purpose of this study was to determine the effect of High Intensity Interval Training (HIIT) on increasing the VO2Max of futsal athletes at SMAN 1 Gerung in 2021. The method used in this study was an experimental method with one group pretest-posttest design. In this study the authors took a sample with a population study that used all 15 futsal athletes. The research instrument used was Multi Stage Fitness (Bleep Test). The results of this data analysis used t-test analysis which resulted in t-count greater than t-table. High Intensity Interval Training (HIIT) exercise with a value of (6.895 > 1.761) so that the Ha hypothesis is accepted and the Ho hypothesis is rejected which reads: "There is an Effect of High Intensity Interval Training (HIIT) on Increasing the VO2Max of Futsal Athletes in SMAN 1 Gerung in 2021"